1996
DOI: 10.1097/00005176-199611000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease in Arabs

Abstract: A systematic study of celiac disease in a defined population of Arab children has not been previously reported. We therefore performed a prospective study to determine the incidence and clinical presentation of celiac disease in Jordanian children. A total of 34 (12 boys and 22 girls) cases were diagnosed over a period of 36 months. Nine cases were clustered in three families. The incidence was calculated to be 1:2,800 live births. The mean age at presentation was 4.6 years (range 0.3-13), but it was 8.4 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 10 publications
2
42
1
Order By: Relevance
“…However, assuming that a later onset is not related to a delayed diagnosis, it is unclear whether an average delay in symptoms of 4 months is clinically relevant, given that the children will still develop the disease. A positive effect of breast-feeding on the onset of celiac disease was observed in some earlier studies [7,[28][29][30][31][32]. However, these studies did not adjust for potential confounders which were shown in our study to bias results for the age at introduction of gluten.…”
Section: Discussionmentioning
confidence: 50%
“…However, assuming that a later onset is not related to a delayed diagnosis, it is unclear whether an average delay in symptoms of 4 months is clinically relevant, given that the children will still develop the disease. A positive effect of breast-feeding on the onset of celiac disease was observed in some earlier studies [7,[28][29][30][31][32]. However, these studies did not adjust for potential confounders which were shown in our study to bias results for the age at introduction of gluten.…”
Section: Discussionmentioning
confidence: 50%
“…In studies from Iran, Iraq, Saudi Arabia and Kuwait, CD accounted for 20% and 18.5% of cases with chronic diarrhea in adults and children, respectively. In a study from Jordan, the high incidence of CD was related to the large wheat consumption of the population (135 kg/head/year) (Rawashdeh et al, 1996).…”
Section: Is Increasingly Reported From the Developing Worldmentioning
confidence: 99%
“…Until the 1980s, coeliac disease (CD) was considered to be very rare in the Middle East [1][2][3] and, based on this assumption, was not considered as a possibility in the differential diagnosis of malabsorption syndromes. 4,5 The discovery that CD is prevalent in the Middle East can be attributed to the judicious use of serological screening tests, which measure antigliadin antibodies (AGA), antiendomysial (EMA) and tissue transglutaminase antibodies (TGA).…”
Section: Epidemiologymentioning
confidence: 99%
“…6 During the last two decades, and following the application of simple serological tests for the diagnosis of CD in Western countries, studies from the Middle East have addressed the prevalence and importance of CD in this region. [1][2][3]5,[7][8][9] According to these studies, the prevalence of CD in different countries of the Middle East (Table 1) was reported to be almost similar to the prevalence of CD in so-called Western countries. The prevalence in at-risk populations in the Middle East is also reported to be much higher than previously thought, ranging between 3 and 20% 10-17 ; the prevalence in individuals with type 1 diabetes is approximately 3-5%.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation